Effective Communication Between Teachers and Parents in Handling Children with Autistic Disorders (Case Study of Handling Autistic Children at Al Azhar 13 Rawamangun Islamic Kindergarten) - Septiyani Endang Yunitasari; Tri Rahayu Budiarti; Lilis Amperawati; Siti Agustiani Rubiah; Ludgardis Mongawara (Institute of Computer Science (IOCS), 2023)
The problem in this study is the lack of effective communication between teachers and parents, so the handling of autistic children is not optimal. The research aims to provide an overview of effective communication between teachers and parents in handling children with autistic disorders to optimize their growth and development. The research method used is descriptive qualitative with a case study focusing on children with autistic disorders at Al Azhar 13 Rawamangun Kindergarten. Data collection was carried out using observation, interview and data documentation techniques. Through this research, it was found that effective communication between teachers and parents has increased the participation of parents in assisting their children, including through conducting two-way communication between teachers and parents, observing and detecting children who have autistic symptoms, recording parents, making agreements with parents to hold scheduled meetings, submitting daily journal reports and communicating through media in the form of telephone, WhatsApp, video recordings. So that parents have more concern and complete attention to the development of their children. While success in children is shown by being able to respond when invited to communicate, socialize, have a sense of comfort in their environment, and reduce tantrum conditions.